1996
DOI: 10.1152/jappl.1996.80.6.2026
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant dysfunction after inhalation of nitric oxide

Abstract: To study whether nitric oxide (NO) affects surfactant function, 36 young rats inhaled one of the following humidified environments for 24 h: 1) air; 2) 95% O2; 3) air and 100 parts/million (ppm) NO; and 4) 95% O2 and 100 ppm NO. The treatments did not change the recovery of phospholipid from bronchoalveolar lavage (BAL). Exposure to NO of animals that breathed either air or 95% O2 increased the minimum surface tension of surfactant from BAL at low (1.5 mumol/ml), but not at high (4 mumol/ml), phosphatidylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 17 publications
0
24
1
Order By: Relevance
“…Interestingly, in a model of acute lung injury from sepsis and hyperoxia, there was no difference in total surfactant levels or large aggregates in lavages between wild and inducible NOS (Ϫ/Ϫ) knockout mice (4). The conflicting results between in vivo and in vitro studies may be explained by the presence of various antioxidants within epithelial lining fluid in vivo not present in vitro, which inactivates the toxic intermediates of NO, such as peroxynitrite (26,27,29,43,60), methemoglobin (30,31,33), and nitrogen dioxide (45), which affect SP synthesis, secretion, or function.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in a model of acute lung injury from sepsis and hyperoxia, there was no difference in total surfactant levels or large aggregates in lavages between wild and inducible NOS (Ϫ/Ϫ) knockout mice (4). The conflicting results between in vivo and in vitro studies may be explained by the presence of various antioxidants within epithelial lining fluid in vivo not present in vitro, which inactivates the toxic intermediates of NO, such as peroxynitrite (26,27,29,43,60), methemoglobin (30,31,33), and nitrogen dioxide (45), which affect SP synthesis, secretion, or function.…”
Section: Discussionmentioning
confidence: 99%
“…Reports regarding the effect of NO in oxidative stress, however, are conflicting (43). In experimental studies, several authors found a worse clinical outcome or surfactant dysfunction as a result of lipid peroxidation or damage to surfactant protein, but they often used very high doses of NO (40 -100 ppm) combined with high and stable FIO 2 levels (80 -100%) (19,43,49). Because of these data, wide use of iNO therapy in preterm infants is unwarranted by most neonatologists (13)(14)(15)50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, iNO may interact with oxygen to form nitrogen dioxide and peroxynitrites, which would enhance pulmonary toxicity. This is a main concern when dealing with premature infants, who already are unable to face oxidant stress (18,19). However, at low dosage and in experimental models, NO is described as antioxidant at the lung level, able to counteract oxidative stress and enhance surfactant function (20,21).…”
mentioning
confidence: 99%
“…Some investigations have shown inhibition of surfactant function by NO [13,14], but the clinical significance of these results is limited by the fact that they were shown in vitro, or in experimental studies with high NO doses. NO affects platelet aggregation, and bleeding complications may be more frequent side effects in premature newborn infants [15].…”
Section: Discussionmentioning
confidence: 99%